1993
DOI: 10.1136/bmj.307.6896.130-b
|View full text |Cite
|
Sign up to set email alerts
|

Patients' satisfaction with psychiatric care.

Abstract: EDITOR,-I C McManus and colleagues rightly emphasise the importance of teaching communication skills, but they do not mention written communication. Sometimes at the end of a consultation the patient is so exhausted and confused that, however good the doctor's communication skills, he or she has difficulty in comprehending the opinion given and the advice proffered. In a randomised trial in the Milton Keynes department of psychiatry, in association with the applied psychology unit of Cranfield College of Aeron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…A study conducted in the U.S. in the early 1980’s found that high quality medical staff was the greatest source of satisfaction, while the cost of care was associated with the most dissatisfaction in a private hospital [9]. Another study in the 1990’s found nurses were seen as the most helpful healthcare professionals patients encountered [10]. While most surveys found psychiatric patient satisfaction was good or high [11, 12], and better than patients with non-psychiatric disorders, some found the contrary.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in the U.S. in the early 1980’s found that high quality medical staff was the greatest source of satisfaction, while the cost of care was associated with the most dissatisfaction in a private hospital [9]. Another study in the 1990’s found nurses were seen as the most helpful healthcare professionals patients encountered [10]. While most surveys found psychiatric patient satisfaction was good or high [11, 12], and better than patients with non-psychiatric disorders, some found the contrary.…”
Section: Introductionmentioning
confidence: 99%
“…14 The majority of our patients have rated the behaviors of doctors and nurses as excellent, similar to prior studies. 5,23,24 In general, patients expect a good rapport with the doctor and expect care, concern, and courtesy in addition to good professionalism. 25 Studies have highlighted the importance of communication between patients and nurses and many have found communication with the nursing team more important to patients possibly because they experience more contact with nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Insofern sind vor allem die nichtklinischen, in der Psychotherapieforschung als "unspezifisch" bezeichneten Wirkfaktoren relevant für die Zufriedenheit des Patienten: "Primäre Bestandteile dieser gemeinsamen unspezifischen Faktoren beinhalten Verständnis, Respekt, Interesse, Ermutigung, Anerkennung, Vergebung -kurz, jene Arten von menschlichen Qualitäten, die schon seit undenkbaren Zeiten als wirkungsvoll im Aufrichten der menschlichen Seele angesehen werden" (Strupp, zitiert nach [5]). Vor diesem Hintergrund verwundert es nicht, wenn Patienten das Pflegepersonal als besonders hilfreich wahrnehmen, weil es verfügbarer ist als Ärz-te oder in einer englischen Studie die Schwestern als größte Hilfe empfunden werden [7].…”
unclassified